The behavior of muzakki in paying zakat; phenomenological study of muzakki's experience in Semarang City - Rohmawati, Siti; Musahadi, Musahadi; Murtadho, Ali (Journal of Islamic Economics Management and Business (JIEMB), 2020)
Purpose – This study aims to determine muzakki's behavior which is reviewed based on the theory of planned behavior, including attitudes towards behavior, subjective norms, and perceived behavioral control.Method – This research used a qualitative research method, while the analytical approach used phenomenological analysis. This study utilized observation and interviews for collecting data. Informants were given a great space to tell their own experiences freely. The number of samples in the study was six informants, i.e., two people who work as civil servants, two people as entrepreneurs, and two people as farmers.Result – Based on the phenomenon and its meaning regarding the behavior of muzakki in paying zakat, it can be concluded that 1) The attitude of the informants tends to comply with the obligation to issue zakat as a form of religious, social, economic, and psychological obedience 2) Informants have subjective beliefs regarding the behavior of paying zakat which is formed from normative beliefs, namely references that come from external and internal parties. 3) Perceptions of behavioral control of the informants. Implication – This study can assist people and organizations in understanding the behavioral aspect of muzakki.Originality – The originality of this research lies in the object under study, test analysis, and research location.